2021
DOI: 10.1098/rsos.210660
|View full text |Cite
|
Sign up to set email alerts
|

Pre-combustion gas separation by ZIF-8-polybenzimidazole mixed matrix membranes in the form of hollow fibres—long-term experimental study

Abstract: Polybenzimidazole (PBI) is a promising and suitable membrane polymer for the separation of the H 2 /CO 2 pre-combustion gas mixture due to its high performance in terms of chemical and thermal stability and intrinsic H 2 /CO 2 selectivity. However, there is a lack of long-term separation studies with this polymer, particularly when it is conformed as hollow fibre membrane. This work reports the continuous measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…One strategy to improve the stability is to functionalize MOF-based membranes to change their resistance for potentially damaging contaminants. Although significant studies have been reported that subjected ZIF-8/polybenzimidazole MMMs to long-term gas separation testing for more than 50 days under more realistic conditions (e.g., in the absence of sweep gas) [205], there have been limited studies investigating the stability of MOF-based membranes.…”
Section: Outlook and Challengesmentioning
confidence: 99%
“…One strategy to improve the stability is to functionalize MOF-based membranes to change their resistance for potentially damaging contaminants. Although significant studies have been reported that subjected ZIF-8/polybenzimidazole MMMs to long-term gas separation testing for more than 50 days under more realistic conditions (e.g., in the absence of sweep gas) [205], there have been limited studies investigating the stability of MOF-based membranes.…”
Section: Outlook and Challengesmentioning
confidence: 99%